Systemic inactivation of TREX1 induces selective inflammation of the tumor microenvironment and invigorated T-cell-mediated tumor control - Marinkovic, Emilija; Chen, Minyi; Schubert, Nadja; Dogan Dar, Elif; Poth, Tanja; Leung, Janet Y.; Lohre, Jack; Sahni, Jennifer M.; Tun, Christine; Rajeswaran, Pavithra; Mehlo-Jensen, Tanja; Perng, Olivia; et al. (Cancer research, 2025)
Therapeutic innate immune-stimulation within the tumor microenvironment can potentiate endogenous antitumor T-cell immunity. Strategies for controlled activation of cGAS/STING signaling are currently under intense investigation. DNase 3′-repair exonuclease 1 (TREX1) is essential for cellular DNA disposal, which prevents autoimmunity ensuing from cGAS/STING activation by endogenous DNA. TREX1-deficient tumor cells elicit enhanced protective immunity in syngeneic models. In this study, we showed that induced inactivation of the Trex1 gene in host (noncancer) cells yields improved type I IFN- and T-cell–dependent control of established TREX1-competent tumors. Host TREX1 deficiency was well tolerated and triggered selective immune cell infiltration into tumors but not into other tissues. Induced systemic loss of TREX1 in tumor-bearing mice resulted in enhanced intratumoral T-cell proliferation and massive increase in numbers of effector and effector-like “exhausted” cells, enabling complete rejection in combination with checkpoint inhibition. To conclude, systemic TREX1 inhibition is a promising approach to boost antitumor immunity and to overcome immune evasion mediated by cancer cell–intrinsic cGAS/STING inactivation.